INFLUENCE OF GROUND DRY ROSE HIPS (Rosa canina L.) ON THE MAIN CHARACTERISTICS OF LACTIC ACID DRINK - IRA TANEVA; MARIYA KALAYDJIEVA; MIHAELA IVANOVA; ZLATIN ZLATEV (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The analysis of available literature sources shows that, in most cases, when obtaining enriched lactic acid products, a fixed amount of rose hip supplement was used, and this amount was not specified. Organoleptic analysis is also missing in many of the publications. Further research is needed to establish the optimal amount of ground rosehip (Rosa canina L.) fruit in the production of lactic acid products using statistical data analysis methods. As a result of the analyzes carried out in the development, the physico-chemical, organoleptic and color characteristics of a lactic acid drink enriched with coarsely ground rose hips and rose hip flour were determined. The informativeness of these characteristics was established, using appropriate statistical methods for the type of data processed. The appropriate amounts of both additives are defined. For the lactic acid drink obtained with coarsely ground rosehip berries, the optimal amount is 2.76 %, and with the addition of rosehip flour it is 0.53 %. The proposed tools can be used in the development of methods for the valorization of waste products from food production and their addition to dairy products.